SINTESIS IONOFOR DTODC SEBAGAI BAHAN AKTIF DALAM ELEKTRODA ION SELEKTIF PENENTUAN MERKURY (ISE-Hg) - Situmorang, Manihar; Purba, Jamalum; Lamria, Melinda Lena; Cintiya, Henni; Sinulingga, Kiki A. Putri Br.; Sihombing, Eidi (JURNAL PENELITIAN SAINTIKA, 2014)
Synthesis of 7,16-dithenoyl-1,4,10,13-tetraoksa-7,16- diazacyclooctadecane (DTODC) as an active material for ion selective electrode mercury (ISE-Hg) is explained. The study is aimed to obtained ionophor DTODC to be used as sensing agent in ISE-Hg for the determination of mercury. The synthesis is carried out through addition and substitution process onto a starting material of 1,4,10,13-tetraoksa-7,16 diazocyclooctadecane (DC). The results showed that pure white crystal of DTODC has been obtained. The target compound has been identified and analysed to confirm its chemical structure. The compound of DTODC has been immobilised into electrode membrane for the construction of ion selective electrode (ISE). The techniques to prepare membrane electrode by using spin coated and casting methods, and the construction procedures to prepare ISE-Hg for determination of mercury have also been studied.